THE IMPLEMENTATION OF SMART FINGERS TECHNIQUE IN IMPROVING STUDENTS’ TENSES MASTERY AT 1ST SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF MATHLA’UL ANWAR UNIVERSITY, BANTEN - Ade Sudirman (Universitas Singaperbangsa Karawang, 2015)
This study aims to investigate theimplementation of Smart Fingers technique in improving students’ tenses mastery at 1stsemester students of English department of Mathla’ul Anwar University, Banten. The research employs the qualitative research design with the characteristics of action research. It uses a triangulation of data collection methods involving questionnaire, observation, and interview. The findings reveal that the implementation of Smart Fingers technique is helpful and easy to conduct. In addition, this technique can improve students’ tenses mastery. In relation to the students’ responses on the technique, it is found that the students respond the technique positively. Moreover, they feel happy and enthusiastic to practice this technique in learning and mastering English tenses. Based on the findings of this research, it is significant for the teachers to choose the appropriate technique for improving students’ tenses mastery, particularly Smart Fingers technique as mentioned above. It is also wise for the teachers to identify the students’ responses on the technique used to determine which technique is appropriate for them. The findings are also expected to encourage other researchers to investigate the effects of this technique on other students’ ability in grammar mastery. Key words: Smart Fingers technique, tenses, grammar.